Comparative study of efficacy and safety of intravenous ferric carboxy maltose versus iron sucrose in treatment of postpartum iron deficiency anemia - Joshi, Suyajna D.; Chikkagowdra, Shaila; CM, Veerendra Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Iron deficiency is the commonest treatable cause of postpartum anemia. Parenteral iron therapy results faster and higher replenishment of iron stores and correction of Hb levels with better compliance. The study was to compare the safety and efficacy of ferric carboxy maltose (FCM) with iron sucrose to treat iron deficiency anemia in the post-partum. Methods: 200 women of postpartum iron deficiency anemia were allocated into two groups. Iron sucrose group, subjects were given I.V. iron sucrose in multiple doses, 200 mg/day on day 0,2,4,6,8 total of 1000 mg. FCM group , subjects were given I.V. ferric carboxymaltose 1000 mg single dose. Both groups Hb%, and serum ferritin were done on 0 and day 30 of last dose of parenteral iron. Side effects, compliance were noted. Results: There was statistically significant rise (P <0.001) of Hb in FCM group 4.68 g/dl compare to iron sucrose group 3.92 g/dl. Mean rise of serum ferritin was 71.07±27.23 and 95.39±45.84 in iron sucrose and ferric carboxy maltose group. No serious adverse events were reported in either the FCM group or Iron sucrose group. Conclusions: Properties like ultra-short duration of treatment, fewer adverse reactions and better compliance makes FCM the first-line drug in the management of postpartum iron deficiency anemia.